The role of parathyroid and bone scintigraphy in detecting multiple parathyroid adenomas with fibrous dysplasia: A case report - Khairunnisa, Alifina; Budiawan, Hendra; Affandi, Erwin; Kartamihardja, Achmad (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Primary hyperparathyroidism is the leading cause of hypercalcemia, usually caused by a parathyroid adenoma and potentially leading to metabolic bone disorders. Fibrous dysplasia is a rare skeletal disorder that can coexist with hyperparathyroidism, although it is rarely found without McCune-Albright syndrome. CASE: A 31-year-old woman with a history of hemodialysis presented with progressive swelling of the upper and lower jaw over the past two years, accompanied by bone pain and fatigue. Laboratory tests revealed elevated parathyroid hormone levels, serum creatinine, and hypocalcemia. Magnetic resonance imaging (MRI) of the neck identified an isointense lesion in the left thyroid gland but failed to localize the parathyroid adenoma. 99mTc-Sestamibi parathyroid scintigraphy showed multiple adenomas in the lower poles of both thyroid lobes. 99mTc-MDP bone scintigraphy demonstrated a metabolic superscan pattern, leading to a diagnosis of primary hyperparathyroidism with polyostotic fibrous dysplasia. The patient underwent minimally invasive parathyroidectomy, which was histopathologically confirmed as bilateral inferior parathyroid adenomas. Postoperatively, the patient experienced significant symptom improvement, including reduced bone pain and improved quality of life. CONCLUSION: The coexistence of primary hyperparathyroidism and fibrous dysplasia without McCune-Albright syndrome is rare but important to recognize. Parathyroid and bone scintigraphy play a crucial role in diagnosis, assessing bone involvement, and planning appropriate therapy. A multimodal imaging approach enables early detection and more effective surgical strategies, improving clinical outcomes for patients.